Rethinking renewable energy policies for hydrogen: How the intercept of electricity and hydrogen markets can be addressed - Daniel Geßner (University of Würzburg, Department of Economics, 2024)
A lot of countries have recently published updated hydrogen strategies, often including more ambitious targets for hydrogen production. In parallel, accompanying ramp-up mechanisms are increasingly coming into focus with the first ones already being released. However, these proposals usually translate mechanisms from renewable energy (RE) policy without considering the specific uncertainties, spillovers, and externalities of integrating hydrogen electrolysis into electricity grids. This article details how different aspects of a policy can address the specific issues, namely funding, risk-mitigation, and the complex relation with electricity markets. It shows that, compared to RE policy, subsidies need to emphasize the input side more strongly as price risks and intermittency from electricity markets are more prominent than from hydrogen markets. Also, it proposes a targeted mechanism to capture the positive externality of mitigating excess electricity in the grid while keeping investment security high. Economic policy should consider such approaches before massively scaling support and avoid the design shortcomings experienced with early RE policy.
urn:nbn:de:bvb:20-opus-370973
Keywords: O25; O38; Q42; Q48; 330; hydrogen policy; renewable energy policy; support mechanisms; contracts for difference